Keterkaitan Industri Manufaktur Berintensitas Teknologi dengan Pendekatan Analisis Input-Output di Jawa Timur - Karlina Sari; Muhammad Arifin (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2014)
The economic crisis in 1998 had caused the decrease in economic growth up to 13% and particularly for industrial sector 11.4%. This shock encouraged local governments, including East Java to actively promote industry by utilizing the available natural resources; processing them into products that have value added. The study intends to see the linkage among technology-intensive industrial sectors before the economic crisis (1994) and after the economic crisis (2006). The analysis method used in the study is input-output (I-0) analysis, using the dispersion power index and the degree of sensitivity index from the multiplier matrix. The classification of manufacturing industry is based on its technology intensity, i.e. high-tech, medium-high-tech, medium-low-tech, and low-tech. The result of the study shows that the seed industry sector in 1994 is the industries with high backward and forward linkages, i.e. the group of basic metal and metal goods industry, and non -pharmaceutical chemical industry. In 2006, however, both industries had only high backward linkage. Furthermore, the industrial group with no potential is the industry with low backward and forward linkages in 1994, i.e. food, beverages, and tobacco industry. Nevertheless in 2006 this low-tech intensity industry became a potential, together with timber and rattan industry, and pharmaceuticals and traditional medicine industry. In 2006, the group with less potentials was the low-tech industry like textile, textile product, leather and footwear industry; and the medium-low-tech industry like oil refining industry; as well as the high -tech industry like, railway, transportation tools and its restoration industry. The shift occurred due to the factors of raw material use (local/import) and capability to produce value added products.